New ground-spider genera and species with annexed checklist of the Gnaphosidae (Araneae) of Israel - Levy, Gershom (Zootaxa, 2009)
The new spiders addressed in this paper complement a series of revisions of the family Gnaphosidae from Israel. New records are reported and two new genera: Leptopilos and Talanitoides are defined.The following new species are described: Berlandina avishur, Drassyllus adullam, Leptopilos levantinus, L. lakhish, Megamyrmaekion magshimim, Micaria galilaea, Phaeocedus mikha, Setaphis mediterranea, Talanitoides habesor, Trachyzelotes miniglossus, Zelotes baram, Z. harmeron, Z. geshur, Z. lehavim, Z. golanensis, Z. adderet, Z. paradderet, Z. naphthalii and Z. zekharya. The unknown mates of Haplodrassus atarot Levy, 2004, Leptopilos tenerrimus (O.P.-Cambridge, 1872) n. comb., L. manolisi (Chatzaki, 2002) n. comb., Megamyrmaekion caudatum Reuss, 1834 (former mis-matched male transferred to M. hula n. nov.), Trachyzelotes stubbsi Platnick & Murphy, 1984, Poecilochroa taborensis Levy, 1998, Z. meronensis Levy, 1998, (former mis-matched female transferred to Z. haifaensis n. nov.), Z. hierosolymitanus Levy, 1998, Z. shaked Levy, 1998, Z. zin Levy, 1998 and Z. sumchi Levy, 1998, are described. Two new synonymies are defined: Leptodrassus leclerci Denis, 1966 = Leptopilos tenerrimus (O.P.-Cambridge, 1872) n. comb., and Zelotes incisupalpis Levy, 1998 = Z. hierosolymitanus Levy, 1998. A checklist of all the Gnaphosidae of Israel is provided.